2002
DOI: 10.1002/hed.10098
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy with or without radiotherapy in patients with locoregionally recurrent nasopharyngeal carcinoma

Abstract: Concurrent chemoradiotherapy for locoregional recurrent NPC seems promising. The morbidity experienced resulted from locoregional disease with few progressing to develop systemic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Cisplatin-based chemotherapy (cisplatin alone or cisplatin plus other one or two anti-tumor drugs, including 5-fluorouracil, paclitaxel and gemcitabine) was administered to 37 patients treated with RT and 44 patients without RT. In the re-RT+/-chemtherapy group, eight patients underwent concurrent chemotherapy, 17 patients underwent induction chemotherapy, and 12 patients underwent both induction and concurrent chemotherapy [ 18 , 19 , 22 , 23 ]. In the non-RT + chemtherapy group, after undergoing two to six cycles of chemotherapy, oral tegafur-uracil or capecitabine was administered to 29 patients for maintenance chemotherapy until disease progression or death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin-based chemotherapy (cisplatin alone or cisplatin plus other one or two anti-tumor drugs, including 5-fluorouracil, paclitaxel and gemcitabine) was administered to 37 patients treated with RT and 44 patients without RT. In the re-RT+/-chemtherapy group, eight patients underwent concurrent chemotherapy, 17 patients underwent induction chemotherapy, and 12 patients underwent both induction and concurrent chemotherapy [ 18 , 19 , 22 , 23 ]. In the non-RT + chemtherapy group, after undergoing two to six cycles of chemotherapy, oral tegafur-uracil or capecitabine was administered to 29 patients for maintenance chemotherapy until disease progression or death.…”
Section: Methodsmentioning
confidence: 99%
“…Then chemotherapy became the alternative treatment method for these patients. However, chemotherapy has been considered a palliative therapy in the salvage treatment of local recurrent disease [ 18 , 19 ]. In fact, the efficacy of chemotherapy in treating advanced local recurrent NPC has not yet been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether patients with rnpc can benefit from adjuvant chemotherapy remains controversial. Wong et al 76 retrospectively analyzed 42 cases of rnpc and showed that, compared with palliative cisplatin-5fu, concurrent chemoradiotherapy followed by adjuvant cisplatin-5fu led to better local control (58% vs. 38%); however, no significant differences in os were observed. Nakamura et al 79 treated 36 rnpc cases with chemoradiotherapy.…”
Section: The Role Of Chemotherapymentioning
confidence: 99%
“…We recently reported our preliminary experience in the use of chemotherapy with and without concurrent RT in such a cohort of patients (7). Otherwise, the use of concurrent chemoradiotherapy for the treatment of patients with locoregional recurrent NPC has not been previously addressed, although its role as primary treatment at initial diagnosis is quite well established (8,9).…”
Section: Introductionmentioning
confidence: 98%